Multi-scale study of CNT and CNT-COOH reinforced epoxy composites: dispersion state, interfacial interaction vs mechanical properties. Issue 4 (3rd April 2021) - Yang, Haitang; Yang, Yanping; Liu, Yu; He, Delong; Bai, Jinbo
ABSTRACT: A precise evaluation of the influence of the dispersion and interface on the mechanical properties is the foundation to fabricate high-performance composites. In this work, original CNTs and carboxylic acid-modified CNTs (CNT-COOH) were chosen as the models, and a multi-scale study of CNTs reinforced epoxy composites was conducted, including the mechanical property test, the dispersion state evaluation and the interface analysis. The interface analysis was conducted by combining scanning transmission electron microscopy (STEM) and electron energy-loss spectroscopy (EELS). A wider interphase region was successfully identified in the CNT-COOH/epoxy than in the CNTs/epoxy composites. In addition, improved dispersion state has been achieved in the CNT-COOH/epoxy composite, which leads to a better mechanical performance for the CNT-COOH/epoxy composite. The successful characterization in multi-scale paves the way for a better understanding of the structure–property relationships in composites.